Collaria columbiensis Carvalho, 1984, a newly recognized synonym of Collaria scenica (Stal, 1859) (Hemiptera: Heteroptera: Miridae) - Ferreira, Paulo Sergio F.; Barreto-Triana, Nancy; Ramírez, Gonzalo Abril (Zootaxa, 2013)
The authors propose a new synonym between Collaria scenica (senior synonym) and Collaria columbiensis (junior syn-onym) based on external morphology and genitalia characteristics of male and female adults of both species. There was no significant difference found to believe that they are two different species.